Endogenous maximal interferon-g production may predict response to interferon-g 1b treatment in patients withidiopathic pulmonary fibrosis - Luppi, F.; Losi, M.; D'Amato, et al., R. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2009)
Background: Idiopathic pulmonary fibrosis (IPF) is an untreatable lung disorder with a mean survival of 3 years after diagnosis.Treatment with interferon-gamma (IFN-g) 1b has been reported to significantly improve lung function and arterial oxygen saturation in a first randomized controlled trial; unexpectedly, these findings have not been confirmed in a subsequent large placebo-controlled randomized study. Another larger placebo-controlled randomized trial has been stopped because data analyzed at interim analysis excluded the possibility that treatment with IFN-g 1b would cause a significant reduction in the risk of death. Methods: Seven Italian male patients diagnosed with IPF were treated with IFN-g 1b (200 μg/die subcutaneously three times a week), accordingly to the indications of the Italian Drug Agency. Based on available studies the response to treatment was pre-defined as changes in either lung function (FVC and DLCO) or oxygen arterial saturation. All patients consented to provide a peripheral blood sample for endogenous IFN-g production measurement with the ELISpot assay before treatment and 6 months thereafter. Results: Four of 7 patients improved or stabilized their lung function after 6 months treatment.Using the ELISpot assay to quantify the maximal production of endogenous IFN-g on peripheral blood samples, these 4 patients had a significantly higher endogenous IFN-g production before therapy, as compared to the 3 patients who deteriorated (91.3±49.6 vs 277.8±34.2 spot forming cells, p=0.023). No significant differences were observed after 6 months of treatment. Discussion: These preliminary results suggest that some IPF patients might benefit from treatment with IFN-g 1b and may help to interpret the results of large randomized trials, suggesting that individual susceptibility could determine clinical response to treatment.